Dynamic Lone Pair Expression as Chemical Bonding Origin of Giant Phonon Anharmonicity in Thermoelectric InTe. (14th February 2023) - Zhang, Jiawei; Ishikawa, Daisuke; Koza, Michael M.; Nishibori, Eiji; Song, Lirong; Baron, Alfred Q. R.; Iversen, Bo B.
Abstract: Loosely bonded ("rattling") atoms with s 2 lone pair electrons are usually associated with strong anharmonicity and unexpectedly low thermal conductivity, yet their detailed correlation remains largely unknown. Here we resolve this correlation in thermoelectric InTe by combining chemical bonding analysis, inelastic X‐ray and neutron scattering, and first principles phonon calculations. We successfully probe soft low‐lying transverse phonons dominated by large In 1+ z‐ axis motions, and their giant anharmonicity. We show that the highly anharmonic phonons arise from the dynamic lone pair expression with unstable occupied antibonding states induced by the covalency between delocalized In 1+ 5 s 2 lone pair electrons and Te 5 p states. This work pinpoints the microscopic origin of strong anharmonicity driven by rattling atoms with stereochemical lone pair activity, important for designing efficient materials for thermoelectric energy conversion. Abstract : For thermoelectric InTe, we reveal dynamic lone‐pair expression as the chemical‐bonding origin of giant phonon anharmonicity and intrinsically ultralow lattice thermal conductivity. Our study provides a first detailed microscopic picture connecting dynamical chemical bonding with giant phonon anharmonicity and ultralow thermal conductivity.